Bancroft's theory and practice of histological techniques - Bancroft, John D.; Layton, Christopher; Suvarna, S. Kim (Churchill Livingstone/Elsevier, 2013)
Suitable for those involved with histological preparations and applications, from the student to the highly experienced laboratory professional, this reference book is also useful for the trainee histotechnologist beginning his career.